(untitled) (Journal of the College of Basic Education, 2022)
Microalbuminuria is strongly associated with risk for cardiovascular disease , it’s a widely recognized , strong and independent risk marker of cardiovascular disease among individuals with diabetes. This study was done in the period from October to December 2014 in the national diabetes center , university of al – Mustansiriya , Baghdad , Iraq. The study groups , one is 50 patients with type 2 diabetes mellitus and cardiovascular disease and the second group is 30 patients with only diabetes mellitus as control , their aged ranged between (45-65 )years. The results were shown an increasing in FBG, HbA1c, hs-CRP, LDL, TG, AIP, Urea, creatinine, and Microalbuminuria in patients compared with control group at ( P<0.001). While the concentration of HDL was significantly lower in patients compared with control group at(P<0.001). There is a positive correlation between AIP and HbA1c, hs-CRP, TG, Urea, creatinine, and Microalbuminuria. So microalbuminuria has become a prognostic marker for cardiovascular disease. K